The influence of negative life events on college students’ suicidal ideation: the mediating role of entity theory and the moderating role of meaning in life - Liu, Dan; Geng, Xiaowei; Zhang, Fuwei; Zhang, Yuan; Li, Xueli (Frontiers in Psychology, 2024)
Suicidal ideation is a desire, thought, or conception that is closely associated with suicide, which is an important risk factor for suicidal behavior. Negative life events may impact college students’ suicidal ideation. According to the suicide susceptibility-stress model, the interaction between susceptibility factors and stressors may influence college students’ suicidal ideation. The present study investigated the role of entity theory and meaning in life in the influence of negative life events on suicidal ideation among college students. A nationwide questionnaire survey was conducted among 938 college students. The Beck Scale for Suicide Ideation, the Implicit Personality Theory Questionnaire, the Adolescent Life Events Scale, and the Meaning in Life Questionnaire were used. The results showed that negative life events were positively correlated with suicidal ideation, entity theory played a mediating role, and meaning in life moderated the mediation of entity theory. Finally, meaning in life and entity theory may bring some benefits to college students; that is, when faced with negative life events, meaning in life and entity theory may attenuate students’ suicidal ideation.